Perancangan UI/UX Aplikasi E-learning Kampus Universitas Stikubank Dengan Menggunakan Metode Design Thinking - Adyaksa, Axeldo Chorwanda Ganggas; Santoso, Dwi Budi; Razaq, Jeffri Alfa (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Stikubank University, located in Semarang, has implemented an E-learning application. However, there have been several user complaints regarding its UI (User Interface) and UX (User Experience). Consequently, this issue has been chosen as the subject of research. The research primarily focuses on redesigning the UI and UX using the Design Thinking methodology, which encompasses the stages of Empathize, Define, Ideate, Prototype, and Test. Data collection was conducted through interviews with a total of 6 participants, comprising 4 students and 2 lecturers. The objective of the research is to determine how appealing and user-friendly the current E-learning application at Stikubank University is. For the testing phase, the researcher utilized the System Usability Scale (SUS) to evaluate the usability of the prototype. The testing results using the SUS get a score of 75.75, which the 'good' category (grade B).